2020
DOI: 10.3390/ijms21197114
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Ceramic Exacerbates the Inflammatory Disease by Activation of Macrophages and T Cells

Abstract: (1) Background: Aluminum oxide (Al2O3) ceramic is one of the materials used for artificial joints, and it has been known that their fine particles (FPs) are provided by the wear of the ceramic. Al2O3 FPs have been shown to induce macrophage activation in vitro; however, the inflammatory effect in vivo has not been studied. (2) Methods: We examined the in vivo effect of Al2O3 FPs on the innate and adaptive immune cells in the mice. (3) Results: Al2O3 FPs promoted the activation of spleen macrophages; however, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Another study revealed the in vivo effect of aluminum oxide fine particles (Al 2 O 3 FPs) on the innate and adaptive immune cells in mice. The researchers found that Al 2 O 3 FPs promoted the activation of spleen macrophages, increasing the number of CD4 and CD8 T cells, which differentiated into interferon-gamma (IFN-γ)-producing helper T1 (Th1) and cytotoxic T1 (Tc1) cells, potentially contributing to the exacerbation of inflammatory diseases [ 6 ].…”
mentioning
confidence: 99%
“…Another study revealed the in vivo effect of aluminum oxide fine particles (Al 2 O 3 FPs) on the innate and adaptive immune cells in mice. The researchers found that Al 2 O 3 FPs promoted the activation of spleen macrophages, increasing the number of CD4 and CD8 T cells, which differentiated into interferon-gamma (IFN-γ)-producing helper T1 (Th1) and cytotoxic T1 (Tc1) cells, potentially contributing to the exacerbation of inflammatory diseases [ 6 ].…”
mentioning
confidence: 99%